Deixis Used in Miley Cycrus’s Song Lyrics “Angels Like You” - Tiara Nurwanti; Endang Susilowati (Universitas An Nuur, 2023)
Deixis is an important part of linguistics and pragmatics, functioning to interpret utterances in context. This study aims to examine the types of deixis used in the lyrics of Miley Cyrus’s most famous song at the time, “Angles like you”. This study employs a descriptive qualitative method. The data are derived from the lyrics of the song. The data are based on the taxonomy of deixis types by Yule (1996). The results reveal that there are four categories of deixis found in this study, namely person deixis, time deixis, and place deixis. Meanwhile, none of the discourse deixis is used. Person deixis is the most commonly used deixis, followed by temporal deixis, spatial deixis, and social deixis. Finally, it is expected that this study may facilitate readers to more easily understand the use of deixis in communication.